The managed economy : papers presented to Section F (Economics) at the 1969 annual meeting of the British Association for the Advancement of Science - Cairncross, Alec; British Association for the Advancement of Science (Oxford : Basil Blackwell, 1970)
The papers in this volume were presented to Section F of the British Association in September 1969 at its Exeter meeting. They deal with problems of economic management.
Includes bibliographical references.
rpm 27/11/2017
Loans
Keywords: Economic policy